The genogram and the ecomap as assessment tools in family medicine: a community experience - Melo Guarín, Astrid Rocío Rocio; Pedraza Orjuela, Aida Faizully (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
Introduction: In Family Medicine, the use of genograms and ecomaps is useful for clinical, family and community practice, in the field of primary health care; however, its role has only been evaluated in the clinical setting. Objectives: To characterize the families participating in the community project from the genograms and ecomaps made by the resident doctors in a neighborhood of the city of Tunja, (Boyacá). Materials and methods: A descriptive cross-sectional study was carried out, compiling information from the genograms and ecomaps applied to the participating families. Results: 49 families were described mainly nuclear, small and bi-generational, with strong internal parental, conjugal and fraternal relationships, with solid external relationships with religion, work and the exterior family. Significant variability was found in the completion of the instruments by the residents. Conclusions: Genograms and ecomaps are instruments that have been used in the clinical context, and are relevant for knowing and analyzing health conditions in the community and family environment, since they can identify weaknesses and strengths, to facilitate the intervention in internal relationships and outside the family.